2022
DOI: 10.3390/ijms23042186
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolite Conjoint Analysis Reveals the Seed Dormancy Release Process in Callery Pear

Abstract: Seed dormancy transition is a vital developmental process for seedling propagation and agricultural production. The process is precisely regulated by diverse endogenous genetic factors and environmental cues. Callery pear (Pyrus calleryana Decne) is an important rootstock species that requires cold stratification to break seed dormancy, but the mechanisms underlying pear seed dormancy release are not yet fully understood. Here, we analyzed the transcriptome profiles at three different stages of cold stratifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…ABA levels are closely related to seed dormancy status. In this study, ABA levels showed a significant decline during the germination process ( Figure 2 ), which was similar to that of red bayberry [ 15 ], celery [ 16 ], ginkgo [ 17 ], and pear [ 18 ]. Concomitantly, the expression profiles of multiple ABA biosynthesis and deactivation genes, including NCEDs and CYP707As, were highly consistent with the dynamics of ABA ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…ABA levels are closely related to seed dormancy status. In this study, ABA levels showed a significant decline during the germination process ( Figure 2 ), which was similar to that of red bayberry [ 15 ], celery [ 16 ], ginkgo [ 17 ], and pear [ 18 ]. Concomitantly, the expression profiles of multiple ABA biosynthesis and deactivation genes, including NCEDs and CYP707As, were highly consistent with the dynamics of ABA ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 71%
“…The specific role of IAA in seed germination may vary between species. Some studies have reported that IAA levels increase during seed imbibition and after ripening in Arabidopsis , pear [ 18 ], and wheat [ 26 ]; on the contrary, more studies have implied that IAA acts through interaction with ABA and thereby inhibits seed germination and pre-harvest sprouting instead of promoting seed dormancy [ 26 ]. In the present study, the trend in IAA content was similar to that of ABA content, which decreased from DS to ES.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosome 8 QTL 2021-qsg8.1 is located between 1,742,525 and1,779,289 bp, a 36.26 Kb region that contains six functional genes. Among them, a potential candidate is a NAC domain-containing protein, which is well-known in plant growth, particularly in seed germination and dormancy (Mathew et al, 2016 ; Kong et al, 2020 ; Zhang et al, 2022c ). Other potential candidate genes, such as the receptor-like protein kinase HSL1, were also located in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that the duration of stratification also affects seed dormancy release. The seed germination rate of pear rapidly increased and reached 85% after 50 days of cold stratification [6]. Moreover, a study of Paris polyphylla showed that seed dormancy release during warm stratification is controlled not only by the temperature but also by the duration of stratification [7], indicating that seed dormancy release is precisely regulated by temperature and time.…”
Section: Introductionmentioning
confidence: 99%
“…In dormant Arabidopsis seeds, alternating temperatures can break dormancy by increasing the expression of GA3ox1 mediated through phytochrome B [12]. Meanwhile, the transcription factors (TFs) ERF, MYB, bHLH, NAC, WRKY, and MADS play important roles in the seed dormancy release of pear during cold stratification [6]. Additionally, the transcription factor ABA INSENSITIVE4 (ABI4) affects the seed dormancy status by targeting genes related to ABA and GA biosynthesis, catabolism, and signal transduction [13,14].…”
Section: Introductionmentioning
confidence: 99%